Mongolian Pre-Service English Teachers' Voices about Their Teaching Practicum Experiences - Daariimaa Marav (MDPI AG, 2022)
Despite the growing uptake of the English language by Mongolian youth and policy initiatives at the governmental level that have emphasized English education, there is very limited internationally available discussion and research on English language teacher education in Mongolia. Thus, the paper aims to examine teaching practicum experiences of pre-service English teachers in Mongolian secondary school settings and explore what challenges they face. Eleven pre-service English teachers, who completed their 12-week teaching practicum in secondary schools in Ulaanbaatar, participated in this study by writing personal narratives on their teaching practicum experiences. The findings indicate that the participants struggled in their teaching contexts due to the lack of mentoring by public school mentor teachers, insufficient university-school partnerships, and classroom-level constraints caused by the mismatch between what they had learned at university and the realities faced in school classrooms. It is recommended to develop a comprehensive teacher development program to improve the quality of both in-service and pre-service English teachers, and to reduce educational inequality associated with access to quality English language education. Furthermore, incorporating social justice education into English teacher preparation programs is important to help future teachers become more critical, reflexive, and transformative.